PH‐ and β‐cyclodextrin‐responsive micelles based on polyaspartamide derivatives as drug carrier. Issue 11 (5th March 2015) - Yu, Huan; Sun, Jian; Zhang, Yunti; Zhang, Guangyan; Chu, Yanfeng; Zhuo, Renxi; Jiang, Xulin
ABSTRACT: A novel kind of graft polymer poly(aspartic acid)‐ethanediamine‐ g ‐adamantane/methyloxy polyethylene glycol (Pasp‐EDA‐ g ‐Ad/mPEG) was designed and synthesized for drug delivery in this study. The chemical structure of the prepared polymer was confirmed by proton NMR. The obtained polymer can self‐assemble into micelles which were stable under a physiological environment and displayed pH‐ and β‐cyclodextrin (β‐CD)‐responsive behaviors because of the acid‐labile benzoic imine linkage and hydrophobic adamantine groups in the side chains of the polymer. The doxorubicin (Dox)‐loaded micelles showed a slow release under physiological conditions and a rapid release after exposure to weakly acidic or β‐CD environment. The in vitro cytotoxicity results suggested that the polymer was good at biocompatibility and could remain Dox biologically active. Hence, the Pasp‐EDA‐ g ‐Ad/mPEG micelles may be applied as promising controlled drug delivery system for hydrophobic antitumor drugs. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2015, 53, 1387–1395 Abstract : A novel polyaspartamide‐based graft polymer containing acid‐labile benzoic imine linkage and adamantine groups in the side chains was fabricated for drug delivery, which can self‐assemble into polymeric micelles showing pH‐ and β‐cyclodextrin responsiveness. The doxorubicin‐loaded micelles are stable under physiological conditions exhibiting a rapid release under acidic or β‐cyclodextrin environment, which displayed comparative anticancer activity to free doxorubicin, whereas blank polymeric micelles were nontoxic.